Consequences of Online Extramarital Relationships from the Men's Perspective: A Qualitative Study - Hajizadeh, Zeinab; Lotfi Kashani, Farah; Vaziri, Shahram; Ahi, Qasem (Applied Family Therapy Journal (AFTJ), 2024)
Objective: The aim of this study is to qualitatively analyze the consequences of online extramarital relationships from the perspective of men.Method: This research was conducted using a qualitative approach, employing content analysis. Based on the principle of theoretical saturation, twelve men participated in this study. Semi-structured interviews were used for data collection, and MAXQDA software was used for coding and categorizing the data.Findings: The consequences of online extramarital relationships among men can be classified into two main categories and five subcategories. The results indicate that hiding the relationship while maintaining marital life, public disclosure, divorce, and separation are among the consequences of online extramarital relationships from the men's perspective.Conclusion: In conclusion, this study highlights the complex dynamics of online infidelity among men in Mashhad, Iran, revealing key themes such as relationship concealment, marital dissatisfaction, and the impact on trust and family stability. The findings underscore the importance of understanding cultural and individual factors in the context of extramarital relationships and provide a foundation for future research on the psychological and relational consequences of online infidelity.